(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Panchakola Choornam is a classical Ayurvedic formulation known for its Deepana and Pachana properties, traditionally used to correct digestive dysfunction and eliminate metabolic waste. This study aimed to validate and standardize the formulation through organoleptic, physicochemical, phytochemical, and TLC analyses. The Choornam exhibited characteristic sensory features and a mildly acidic pH (5.95), supporting its digestive role. Phytochemical screening confirmed the presence of glycosides, phenols, alkaloids, flavonoids, and coumarins, with water extracts highlighting hydrophilic constituents. TLC fingerprinting showed strong correlation with individual ingredients, ensuring formulation integrity, and revealed unique markers suggesting synergistic interactions. These findings affirm the safety, efficacy, and traditional use of Panchakola Choornam, providing a scientific basis for its standardization and future integration into evidence-based Ayurvedic practice.